2023
DOI: 10.1021/acs.est.2c04705
|View full text |Cite
|
Sign up to set email alerts
|

Land–Water Transport and Sources of Nitrogen Pollution Affecting the Structure and Function of Riverine Microbial Communities

Abstract: The characterization of variations in riverine microbiota that stem from contaminant sources and transport modes is important for understanding biogeochemical processes. However, the association between complex anthropogenic nitrogen pollution and bacteria has not been extensively investigated owing to the difficulties faced while determining the distribution of nitrogen contaminants in watersheds. Here, we employed the Soil and Water Assessment Tool alongside microbiological analysis to explore microbial char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…After returning to the lab, both of them were filtered through a 0.45 μm membrane, characterized, and then stored at 4 °C. 46 The pH (7.34 ± 0.03 vs 7.75 ± 0.10), TOC (2.26 mg/L vs 3.65 mg/L), and electric conductivity (194.3 ± 0.5 μS/cm vs 391.6 ± 1.0 μS/cm) of the Xiangjiang sample were lower than those of the Taozihu one. They have the same most abundant univalent (Na + ) and divalent (Ca 2+ ) cations and anions (SO 4 2− ) (Table S1).…”
Section: Irradiation Experimentsmentioning
confidence: 85%
See 1 more Smart Citation
“…After returning to the lab, both of them were filtered through a 0.45 μm membrane, characterized, and then stored at 4 °C. 46 The pH (7.34 ± 0.03 vs 7.75 ± 0.10), TOC (2.26 mg/L vs 3.65 mg/L), and electric conductivity (194.3 ± 0.5 μS/cm vs 391.6 ± 1.0 μS/cm) of the Xiangjiang sample were lower than those of the Taozihu one. They have the same most abundant univalent (Na + ) and divalent (Ca 2+ ) cations and anions (SO 4 2− ) (Table S1).…”
Section: Irradiation Experimentsmentioning
confidence: 85%
“…Although close in distance, they are typically flowing and enclosed waters, respectively. After returning to the lab, both of them were filtered through a 0.45 μm membrane, characterized, and then stored at 4 °C . The pH (7.34 ± 0.03 vs 7.75 ± 0.10), TOC (2.26 mg/L vs 3.65 mg/L), and electric conductivity (194.3 ± 0.5 μS/cm vs 391.6 ± 1.0 μS/cm) of the Xiangjiang sample were lower than those of the Taozihu one.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic activities have shown an impact on both hydrological patterns and pollutant discharge within watersheds [6]. Microbes in these nutrient sources potentially alter the biogeochemical processes and lead to N 2 O emissions in waters to the atmosphere, which can, in turn, affect nitrification and denitrification processes [6][7][8]. Furthermore, increasing discharges of excessive fertilizers from farming lands, residential lawns, and effluent discharge gradually led to the eutrophication of Utah Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the urbanized river network of Chongqing and Shanghai metropolitan areas, China, provided clear evidence that extensive pollutants generally strengthen CO 2 emissions from urban rivers (X. Wang et al., 2017; Yu et al., 2017). On the other hand, the discharge of municipal sewage and industrial effluents with high dissolved inorganic carbon (DIC) and alkalinity (J. Wang et al., 2021) and active sewage‐treatment microbes (Hiruy et al., 2022; Zhu et al., 2023) could directly or indirectly elevate CO 2 saturation and evasion (Chanda et al., 2020; Luo et al., 2019; J. Wang et al., 2021; Yu et al., 2017). Previous studies have suggested that watershed urbanization could transform rivers into enhanced heterotrophy systems (Gong et al., 2019; X. Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2017;Yu et al, 2017). On the other hand, the discharge of municipal sewage and industrial effluents with high dissolved inorganic carbon (DIC) and alkalinity (J. and active sewage-treatment microbes (Hiruy et al, 2022;Zhu et al, 2023) could directly or indirectly elevate CO 2 saturation and evasion (Chanda et al, 2020;Luo et al, 2019;Yu et al, 2017). Previous studies have suggested that watershed urbanization could transform rivers into enhanced heterotrophy systems (Gong et al, 2019;X.…”
mentioning
confidence: 99%